2011
DOI: 10.1164/rccm.201011-1854ci
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Thromboembolic Pulmonary Hypertension

Abstract: C hronic thromboembolic pulmonary hypertension (CTEPH) has emerged as one of the leading causes of severe pulmonary hypertension. The disease is notoriously underdiagnosed, and the true prevalence is still unclear. CTEPH is characterized by intraluminal thrombus organization and fibrous stenosis or complete obliteration of pulmonary arteries. 1 The consequence is an increased pulmonary vascular resistance resulting in pulmonary hypertension and progressive right heart failure. Vascular disobliteration by pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
213
0
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(233 citation statements)
references
References 77 publications
(85 reference statements)
2
213
0
18
Order By: Relevance
“…1,2 Although the incidence of CTEPH is usually estimated to be <1% among patients with acute PE, [2][3][4] several studies have proposed that this low incidence was an underestimation and showed approximately 4%, a relatively high incidence of CTEPH after PE. [5][6][7] In addition, it has not been shown why some PE patients develop CTEPH and others do not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Although the incidence of CTEPH is usually estimated to be <1% among patients with acute PE, [2][3][4] several studies have proposed that this low incidence was an underestimation and showed approximately 4%, a relatively high incidence of CTEPH after PE. [5][6][7] In addition, it has not been shown why some PE patients develop CTEPH and others do not.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that the majority of acute PE patients do not go on to develop CTEPH suggests that there are actually other factors that are important in the development CTEPH. 2 Therefore, it is important to determine the possible risk factors and/or predictors for the CTEPH in patients with PE in order to decrease the morbidity and mortality of CTEPH.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by stenoses and obstruction of the pulmonary arteries caused by organized thrombus 1, 2, 3, 4, 5. Without being treated, the prognosis is so poor that a 5‐year survival rate in patients with a mean pulmonary artery pressure (mPAP) >50 mm Hg is 10% 6.…”
mentioning
confidence: 99%
“…CTEPH is related to an increase in the resistance to flow through the pulmonary arteries, which results initially from obstruction of pulmonary arterial vessels from main to subsegmental levels by analyzed thromboembolic materials, and subsequently from vascular remodeling in small unobstructed vessels. Previous studies (43)(44)(45)(46)(47)(48)(49) have reported that improvement in conventional parameters such as CI, 6-MWD, mPAP, and/or PVR showed significant differences between the responder and nonresponder groups, and suggested their usefulness for disease severity assessment and/or treatment response evaluation for CTEPH patients in routine clinical practice. Our results for conventional parameters were comparable with those reported in the past literature for CTEPH patients undergoing drug therapy (43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 96%
“…However, our results demonstrated that improvements in CTEPH MRA and PBF showed better correlation with conventional parameters than did improvements in RV/LV diameter ratio, CTEPH CTA , PBV, and MTT. According to several pharmacological reports (43)(44)(45)(46)(47)(48)(49), improvement due to drug therapy is theoretically observed at small vessels in the lung parenchyma and as improved lung peripheral perfusion. Although CTEPH CTA and CTEPH MRA can both qualitatively assess lung parenchyma perfusion, CTEPH MRA is more affected by lung parenchyma perfusion changes than CTEPH CTA because it shows a reduction in perfusion as well as clots in the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%